Biological Activity of Annona muricata Seed Extracts - Hoe, P.K; Yiu, P.H.; G.C.L., Ee; Wong, S.C.; A, Rajan; Bong, C.F. (Malaysian Journal of Science, 2010)
A study was conducted to assess the biological activity of Annona muricata hexane, methanol and chloroform seed extracts. Both the hexane and methanol extracts showed moderate larvicidal activity against the Aedes aegypti larvae while the chloroform extract exhibited strong larvicidal property with an LC50 value of 0.9005µg/ml and an LC90 value of 6.1776µg/ml. Fraction 44b and 45b of the chloroform extracts were very toxic towards mosquito larvae with LC50 values of 0.7460 and 1.0402µg/ml, respectively. Identification of bioactive compounds revealed the presence of solamin, an acetogenin. From the cytotoxic assay against brine shrimp (Artemia salina), the methanol extract showed high toxicity with an LC50 value of 11.8823µg/ml. The results suggest potential application of the extracts in insecticidal formulations. Satu kajian aktiviti biologi telah dijalankan pada ekstrak-ekstrak heksana, methanol dan klorofom biji Annona muricata. Ekstrak-ekstrak heksana dan methanol menunjukkan aktiviti larvisidal sederhana terhadap larva Aedes aegypti manakala, ekstrak klorofom mempamerkan sifat larvisidal yang kuat dengan nilai LC50 0.9005µg/ml dan LC90 6.1776µg/ml. Fraksi 44b dan 45b ekstrak klorofom sangat toksik dengan nilai LC50 0.7460 dan 1.0402µg/ml masing-masing. Kewujudan sebatian bio-aktif solamin, sejenis acetogenin telah dikenali-pasti. Dalam ujian citotoksik pada udang laut (Artemia salina), ekstrak metanol menunjukkan ketoksikan tinggi dengan nilai LC50 11.8823µg/ml. Hasil kajian mencadangkan ekstrak berpotensi dalam formulasi-formulasi racun serangga.